TINJAUAN FATWA DEWAN SYARIAH NASIONAL TERHADAP ANALISIS IMPLEMENTASI AKAD MURABAHAH - Hakim Muslim Soli (Program Studi Perbankan Syariah, 2020)
This study aims to determine the implementation of the murabahah contract at the Prosumen Amanah Mandiri BMT based on a fatwa from the DSN. This type of research is qualitative research. This research was collected through observation, interviews and documentation. The respondents in this study amounted to 6 (six) people. The respondents included 3 (two) people from the Mandiri Prosumen Amanah BMT and 3 (people) customers. The results showed that the implementation of the mur??bah??ah contract at the PAM BMT had its standard operational procedures by OJK provisions. The implementation of the mur??bah??ah contract at BMT PAM is by the Fatwa of the National Sharia Council NO.04 / DSN-MUI / IV / 2000 concerning the mur??bah??ah looking at the mechanism of the procedure for implementing the mur??bah??ah contract at BMT PAM.